THE INFLUENCE OF AUDITOR QUALITY AND GOOD CORPORATE GOVERNANCE ON THE QUALITY OF FINANCIAL STATEMENTS - Elis Purnamaningsih; Yuniati, Triana; Rohaeni, Heni; Noor Fikri, adi Wibowo (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research aims to analyze the influence of auditor quality and good corporate governance on the quality of financial reports. The research method used is a quantitative research method with a descriptive and verification approach. The sample in this research was 45 banking companies that were listed on the Indonesia Stock Exchange (BEI) in 2019-2021. The audit quality variable is proxied using the type of public accounting firm,good corporate governance protected using institutional ownership, board of commissioners and audit committee, while the quality of financial reports is proxied using return of equity, namely profit divided by equity. Hypothesis testing is carried out using descriptive statistical methods, classical assumption testing, multiple linear regression analysis, and hypothesis testing. Until 2021, there will be 78 observations of financial report data and audit reports. The results of the hypothesis test show that auditor quality and good corporate governance have a significant effect on the quality of financial reports.